Analysis of Factors Influencing Middle-aged and Elderly People’s Decisions of Investment and Financial Management - Xumei, Chen; Xinyan, Yin; Wei, Qiu; Jiamin, Qian; Xiaofeng, Zhang; Chi, Qishui (Archives of Business Research, 2022)
In this paper,we took middle-aged and elderly people as the research objects and collected the influence degree data of factors affecting the investment and financial decision-making through questionnaire,then applied statistical methods and the analytic hierarchy process to determine the primary and secondary ranking of the influence degree of these influencing factors.This study may provide reference for middle-aged and elderly people doing investment and financial management, financial institution constructing platform and developing product,government supervision,etc.We found that the most important factor affecting the investment and financial decisions of middle-aged and elderly people is the system stability in the platform factors,followed by the professional guidance in the personal characteristics and the operation difficulty in the platform factors.